Model predictive control-based wind turbine blade pitch angle control for alleviation of frequency fluctuation in a smart grid - Pahasa, Jonglak; Ngamroo, Issarachai (My University, 2014)
This paper proposes model predictive control (MPC) for wind turbine blade pitch angle control of a smart grid. The MPC is an effective model-based predictive control which calculates future control signals by optimization method using plant model, current and past signals of the system. The MPC-based blade pitch angle control is used for smoothing of wind power production of wind turbine generator. As a result, the frequency fluctuation in the smart grid system resulted from wind power deviation can be maintained. The simulation results performed in a two-area interconnected power system show that the MPCs-based blade pitch angle of wind turbine generator is capable to reduce frequency fluctuation on the study system.
Keywords: blade pitch angle; Model predictive control; smart grid; wind turbine generator